Optimization of Bhabinkamtibmas Performance in the Framework of Maintaining Public Security and Order in the Legal Area of Karanganyar Police - Tegar Mulia Nst (Tanggon Kosala, 2023)
The crime of theft with weighting still dominates the list of kamtibmas disturbances in the jurisdiction of the Pekalongan Police. The Pekalongan Resort Police through the Samapta Unit has a major role in controlling and preventing cases of weighted theft by carrying out preventive efforts through patrols. The implementation of routine patrols is efficient but not optimal, this can be seen from the number of Curat crimes in the Pekalongan Police area, which is still fluctuating in the last 5 years. This situation motivated researchers to conduct more in-depth research on the topic of Optimizing Patrols by the Pekalongan Police Samapta Unit to Prevent Crime of Theft with Weights in the Framework of Maintaining Kamtibmas. The research was conducted using a qualitative research approach with the type of case study, which means that the researcher places himself as a research subject by going directly into the field. This research is also supported by data collection techniques in the form of observations, interviews, and documentation studies through documents. Then the data that has been obtained is then validated for truth through triangulation and determining the data to be used through data reduction, data presentation, and determining conclusions. The research findings are then analyzed further and then analyzed using the theory of performance achievement factor theory management, SWOT theory. In the end, the researcher was able to find the problem and was able to answer it through the symptoms that occurred in the form of patrol consistency which was assessed based on the Regulation of the Head of the Security and National Police of the Republic of Indonesia Number 1 of 2017 concerning patrols. Patrol is one of the effective preventive efforts when viewed from the process, but maximum results cannot be shown optimally in a sustainable manner. This is influenced by internal and external factors of the Police